Visualizing the early infection of Agathis australis by Phytophthora agathidicida, using microscopy and fluorescent in situ hybridization. Issue 6 (25th March 2016) - Bellgard, S. E.; Padamsee, M.; Probst, C. M.; Lebel, T.; Williams, S. E.
Summary: Phytophthora agathidicida (PTA) causes a root rot and collar rot of New Zealand kauri ( Agathis australis ). This study developed techniques to visualize early infection of kauri by PTA in deliberately inoculated seedlings. Conventional light microscopy was carried out on cleared and stained roots using trypan blue to observe PTA structures. Additionally, scanning electron microscopy (SEM) was used to study the PTA root structures at a higher resolution. A fluorescent in situ hybridization assay (FISH) was developed using a PTA‐specific probe to label PTA structures in planta . Infection progression in roots of 2‐year‐old kauri inoculated with PTA at 5, 10, 16 and 20 days post‐inoculation (d.p.i.) was compared using these three approaches. Light microscopy identified no Phytophthora‐ like structures in the control treatments. In PTA‐inoculated plants, lignitubers were produced 5 d.p.i. in cortical cells. Infection was localized after 5 days, but as the infection progressed (up to 20 d.p.i.), the 'degree' of root infection increased, as did the number of replicates in which structures were observed. SEM provided higher resolution images; again, no PTA structures were observed in the negative control material examined. The slide‐based FISH‐specificity assay successfully hybridized with PTA hyphae. Fluorescence was observed using 330–380 nm excitation and an emission filter at 420 nm (DAPI), with PTA nuclei fluorescing a bright greenish‐yellow. Cross‐reactivity was not observed when the assay was applied to six other non‐target Phytophthora species. Successful hybridization reactions occurred between the primer and PTA structures in planta . Applying this FISH assay has allowed clear differentiation of the intracellular and intercellular structures of PTA. The technique can be applied to longer term studies or analysis of ex situ inoculation studies aiming to elucidate differential host‐responses to the pathogen. Additionally, the technique could be applied to study the interactions with other fungal endophytes (e.g. mycorrhizal fungi), which could be assessed for biocontrol potential as part of the integrated management of the disease.